What is a zero trust network? (O'Reilly, 2017)
"In this video, Doug Barth and Evan Gilman describe what a zero trust network is, and why it is the natural evolution from the current best practice security models. Current network infrastructures are designed to protect your internal network with a firewall, and everything behind that firewall being "trusted" by default. zero trust networks are based on the philosophy that no network is trusted, be it external or internal. In this video, Doug and Evan discuss topics such as why it is important to move to a zero trust network model, what is driving the need to evolve security models, and what some of the benefits are for this type of network security model."--Resource description page